REPRODUCTIVE DISORDERS IN DECCANI EWES: AN ABATTOIR STUDY - SUDHAKAR, T; RAO, K SADASIVA; RAJU, K G SOLMON; ANJANEYULU, Y (The Indian Journal of Animal Reproduction, 2023)
An abattoir survey of 3004 genital tracts of Deccani breed ewes revealed gravid ( 1.06 per cent)and abnormal genital tracts (6.52 per cent). The incidences of anatomical and pathological abnormalitieswere 2.94 and 3.4 per cent, respectively. Among the percentage of anatomical abnormalities, Parovariancyst {1.89), kinked cervix (0.99) and hypoplasia of ovaries (0.06) 1;yere noticed. The incidence ofpathological abnormalities (per cent) were ovarian cysts (0.12), ovaro burs al adhesions (0.49), ovulationtags {0.13}, endometritis (0.76), pyometra (0.49), melanin pigmentation (0.66), hydrometra (0.03),mummification (0.06) and maceration (0.03).
Keywords: Abattoir study; Deccani Ewes; Reproductive disorders